تطوير تطبيق قاموس أندرويد للأفعال اليومية في ترقية مفردات الطلاب لفصل العاشر بمدرسة نهضة الوطن كورليكوا الثانوية. - Zuhry, Asriandi (Lughatu Ad-dhat, 2025)
The quality of a person's language depends on the quality and quantity of their vocabulary. Because the more vocabulary one has, the greater the possibility of mastering language skills. After conducting observations, researchers found that some students still think that learning, remembering or memorizing vocabulary is very difficult, complicated and difficult because it is caused by several factors including: learning resources, teaching materials, learning media, and dictionary books that seem thick and boring because their contents are still classified as complex and not focused on certain problems. therefore, researchers developed an android-based af'al yaumiyah dictionary application to make it easier for students to learn vocabulary. The objectives of this study are: (1) To Know the Development Process of the Android-Based Af'al Yaumiyah Dictionary Application in Improving Vocabulary Mastery of Class X MA NW Korleko Students. (2) To Know the Effectiveness of Using the Android-Based Af'al Yaumiyah Dictionary Application in Improving Vocabulary Mastery of Class X MA NW Korleko Students. The research method used is R&D (Reseach and Devlopment) with the Borg & Gall model. The number of respondents or students used as research samples was 26 students. Data collection was carried out in several stages, namely, observation, documentation, questionnaires and tests. The results of this study are: (1) The process of developing Android-based Af'al Yaumiyah Dictionary Application Products starts from collecting supporting data then proceeds with the design of the user interface and user experience. After the design is complete, then validation is carried out to material experts and media experts. Based on the data from the material expert validation, the percentage obtained is 82.3% and the media expert is 95.55% and refers to the eligibility criteria, each validation from the expert gets a very feasible predicate and the student response gets a rating of 96.59% which shows this product is very good. (2) The effectiveness of using the product to improve students' mastery of Arabic is known from the results of the paired sample t-test which produces a t-count (6.989) which is greater than the t-table (2.060) then Ho is rejected and Ha is accepted. Thus, there is an effect of using the Android-based Af'al Yaumiyah dictionary application in improving students' mastery of Arabic vocabulary. Keywords : Application, Dictionary, Vocabulary